Isolation of Mycobacterium tuberculosis from livestock workers and implications for zooanthroponotic transmission in Ibadan, South-western Nigeria (2018)
Introduction. Tuberculosis (TB) remains a public health problem in sub-Saharan Africa coupled with dearth of information about the disease among livestock workers at risk of infection. We determined the prevalence of pulmonary TB infection and factors associated with its occurrence among livestock workers in south-western Nigeria. Methods. A cross-sectional study was conducted using active case-finding among livestock workers with sub-clinical pulmonary TB between August 2014 and March 2015. Sputum samples were cultured and subjected to a two-step multiplex-PCR technique based on genus-typing and genomic regions-of-difference. Interviewer-administered questionnaire was utilized in assessing worker’s TB related knowledge and practices. Data were analysed using STATA 12. Results. Overall, 206 livestock workers (traders = 136; butchers = 70) were screened; 5.1% (7/136) of the traders and 7.1% (5/70) of the butchers had positive mycobacterial cultures. Molecular techniques identified one Mycobacterium tuberculosis with six non-tuberculous mycobacteria (NTM) from the traders and four M. tuberculosis with one NTM from the butchers. Participants within the age range of 50 years and above were at higher risk of being infected with TB (OR = 7.7; 95% CI: 1.7- 35.6) and majority had poor knowledge and practices regarding TB. Conclusions. We confirmed M. tuberculosis as the cause of pulmonary TB among the livestock workers, with implications for zooanthroponotic transmission of the disease along the humananimal ecosystem interface in Nigeria.